2017
DOI: 10.1111/ans.14154
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of perioperative, renal and oncologic outcomes in robotic‐assisted versus open partial nephrectomy

Abstract: We present the largest reported Australian series on partial nephrectomy, confirming that a robotic-assisted approach is equivalent to OPN, with reduced complications, EBL, length of hospital stays and fewer positive margins, even when resecting more complex tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
(65 reference statements)
1
10
0
Order By: Relevance
“…Remarkably, positive surgical margins were not observed in any RAPN case and in two OPN cases only (2.6%). Hence, the current PSM rates are below the reported range of 3‐12% for endophytic tumors across both approaches and strengthen the evidence that both techniques may offer an oncologically save resection even in highly challenging tumors . The complication rates in this study are relatively high compared to previous studies most likely reflecting the unique patient selection .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Remarkably, positive surgical margins were not observed in any RAPN case and in two OPN cases only (2.6%). Hence, the current PSM rates are below the reported range of 3‐12% for endophytic tumors across both approaches and strengthen the evidence that both techniques may offer an oncologically save resection even in highly challenging tumors . The complication rates in this study are relatively high compared to previous studies most likely reflecting the unique patient selection .…”
Section: Discussionsupporting
confidence: 55%
“…Hence, the current PSM rates are below the reported range of 3-12% for endophytic tumors across both approaches and strengthen the evidence that both techniques may offer an oncologically save resection even in highly challenging tumors. 8,18,[21][22][23] The complication rates in this study are relatively high compared to previous studies most likely reflecting the unique patient selection. 24 Most interestingly, many studies report lower complication rates for RAPN.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty‐four eligible studies included 60 808 patients who underwent PN, of whom 19 638 underwent RaPN with mean age 58.9 years and 41 170 underwent OPN with mean age 58.5 years. Table presents the baseline patient demographics of all enrolled studies.…”
Section: Resultsmentioning
confidence: 99%
“…showed reduced blood loss, ischaemia time, transfusions rate and length of stay for highly complex renal masses. An Australian group also demonstrated reduced complications, estimated blood loss, length of hospital stays and fewer positive margins . Moreover, Camp et al .…”
mentioning
confidence: 93%
“…An Australian group also demonstrated reduced complications, estimated blood loss, length of hospital stays and fewer positive margins. 16 Moreover, Camp et al 17 showed a significant reduction in costs at 1 year post-intervention following RAPN compared to OPN.…”
mentioning
confidence: 99%